2022
DOI: 10.1088/1361-648x/ac4eaf
|View full text |Cite
|
Sign up to set email alerts
|

Compressed superhydrides: the road to room temperature superconductivity

Abstract: Room-temperature superconductivity has been a long-held dream and an area of intensive research. The discovery of H3S and LaH10 under high pressure, with superconducting critical temperatures (Tc) above 200 K, sparked a race to find room temperature superconductors in compressed superhydrides. In recent groundbreaking work, room-temperature superconductivity of 288 K was achieved in carbonaceous sulfur hydride at 267 GPa. Here, we describe the important attempts of hydrides in the process of achieving room tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 139 publications
0
13
0
Order By: Relevance
“…Notwithstanding cold reality, theorists display enormous confidence that their predictions for superconducting materials and their T c 's are valid and reliable [219]. Some statements in recent theoretical papers predicting new hydrides:…”
Section: Complementarity Between Theoretical Prediction and Experimen...mentioning
confidence: 99%
“…Notwithstanding cold reality, theorists display enormous confidence that their predictions for superconducting materials and their T c 's are valid and reliable [219]. Some statements in recent theoretical papers predicting new hydrides:…”
Section: Complementarity Between Theoretical Prediction and Experimen...mentioning
confidence: 99%
“…For example, cuprate high-temperature superconductor HgBa 2 Ca 2 Cu 3 O 8+δ with critical temperature (T c ) of 133 K was discovered [1], whose T c was improved to 164 K in diamond anvil cells [2]; the T c of Bi 2 Sr 2 CaCu 2 O 8+δ was altered from 84 K to 94 K via a shockwave treatment [3]. Recently, many hydrides with T c s exceeding 200 K were discovered under high pressure [4][5][6], e.g., H 3 S with 203 K at 155 GPa [7][8][9][10] and LaH 10 with 250-160 K at 170 GPa [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that compressed hydrogen-rich compounds are potential high-temperature even room temperature superconductors in which the high electronic density of states (DOS) and strong electron–phonon coupling (EPC) driven by hydrogen element dominate the superconductivity . Until now, nearly all binary hydrides have been investigated theoretically or experimentally and some of them exhibit outstanding superconductivity with a critical temperature above 200 K, such as covalent hydrides (H 3 S) and ionic hydrides (LaH 10 , ThH 10 , CaH 6 , YH 6 , etc. ). ,, Interestingly, many ionic hydrides have unique clathrate hydrogen sublattices which are prevalent in alkaline earth and rare earth metal superhydrides.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, nearly all binary hydrides have been investigated theoretically or experimentally and some of them exhibit outstanding superconductivity with a critical temperature above 200 K, such as covalent hydrides (H 3 S) and ionic hydrides (LaH 10 , ThH 10 , CaH 6 , YH 6 , etc. ). ,, Interestingly, many ionic hydrides have unique clathrate hydrogen sublattices which are prevalent in alkaline earth and rare earth metal superhydrides. Some of them have been synthesized experimentally and exhibit high T c .…”
Section: Introductionmentioning
confidence: 99%